Density, habitat use, and opportunities for conservation of shorebirds in rice fields in southeastern South America - Dias, Rafael Antunes; Blanco, Daniel E.; Goijman, Andrea Paula; Zaccagnini, Maria Elena (Bioone, 2018)
Worldwide, shorebirds are a major component of rice field avian biodiversity. Rice fields in Argentina and southern Brazil hold large numbers of shorebirds and have been recognized as important areas for migrating or wintering species. To develop successful shorebird conservation strategies, we need to understand geographic variation in shorebird abundance in rice fields as well as how bird use of rice fields varies over the rice growing cycle. We surveyed shorebirds in November and December in the main rice cultivation regions of interior Argentina and coastal Brazil to estimate shorebird densities using distance sampling and to evaluate densities of individual species at different stages of the rice cycle. We detected >7,000 shorebirds in rice fields, including a variety of Nearctic migrants. Density of resident species was generally low and showed no differences between countries. Densities of migratory taxa were higher and varied between Brazil and Argentina. Pectoral Sandpiper (Calidris melanotos) and Lesser Yellowlegs (Tringa flavipes) were the most common species in Argentina, but White-rumped Sandpiper (Calidris fuscicollis) and American Golden-Plover (Pluvialis dominica) were the most common species in Brazil. Pectoral Sandpiper density was nearly 8 times higher in Argentina than in Brazil; densities of the White-rumped Sandpiper and American Golden-Plover were 33 and 25 times higher in Brazil than in Argentina. Shorebird density was highest in lightly flooded paddies with rice height <20 cm. Our findings confirm the importance of rice paddies for shorebirds in southeastern South America and emphasize the need for detailed assessments to ensure that agricultural chemical and water management practices are biodiversity friendly.